Hubungan Kadar Hemoglobin Ibu Hamil dengan Berat Bayi Lahir (Literature Review) - Rina Setyawati; Nur Afni Wulandari Arifin (Syntax Corporation Indonesia, 2022)
Lack of hemoglobin (Hb) levels in pregnant women is a health problem that often occurs during pregnancy. A hemoglobin (Hb) level of less than 11 g/dl can indicate that pregnant women suffer from anemia. Anemia in pregnant women can increase the risk of giving birth to babies with low birth weight (LBW), the risk of bleeding before and during delivery, and can even cause death of the mother and baby if the mother has severe anemia. The purpose of this study was to determine the relationship between pregnant women's Hb levels and birth weight. This research was conducted by conducting a literature review from research journals related to the research topic, namely the relationship between Hb levels in pregnant women and birth weight. Based on literature studies from several studies, it can be concluded that low hemoglobin levels in pregnant women can increase the risk of having a low birth weight baby (LBW) because blood flow to the uterus is reduced, thereby blocking the flow of oxygen and nutrients to the placenta and fetus. However, in other studies, it can also be concluded that in addition to lack of hemoglobin levels in pregnant women, there are several other factors that can affect the occurrence of LBW such as severe illness, pregnancy complications, malnutrition, and stress conditions in pregnant women